New bacterial pathway for 4- and 5-chlorosalicylate degradation via 4-chlorocatechol and maleylacetate in Pseudomonas sp. strain MT1 - Nikodem, Patricia; Hecht, Volker; Schlömann, Michael; Pieper, Dietmar H (Journal of bacteriology, 2003)
Pseudomonas sp. strain MT1 is capable of degrading 4- and 5-chlorosalicylates via 4-chlorocatechol, 3-chloromuconate, and maleylacetate by a novel pathway. 3-Chloromuconate is transformed by muconate cycloisomerase of MT1 into protoanemonin, a dominant reaction product, as previously shown for other muconate cycloisomerases. However, kinetic data indicate that the muconate cycloisomerase of MT1 is specialized for 3-chloromuconate conversion and is not able to form cis-dienelactone. Protoanemonin is obviously a dead-end product of the pathway. A trans-dienelactone hydrolase (trans-DLH) was induced during growth on chlorosalicylates. Even though the purified enzyme did not act on either 3-chloromuconate or protoanemonin, the presence of muconate cylcoisomerase and trans-DLH together resulted in considerably lower protoanemonin concentrations but larger amounts of maleylacetate formed from 3-chloromuconate than the presence of muconate cycloisomerase alone resulted in. As trans-DLH also acts on 4-fluoromuconolactone, forming maleylacetate, we suggest that this enzyme acts on 4-chloromuconolactone as an intermediate in the muconate cycloisomerase-catalyzed transformation of 3-chloromuconate, thus preventing protoanemonin formation and favoring maleylacetate formation. The maleylacetate formed in this way is reduced by maleylacetate reductase. Chlorosalicylate degradation in MT1 thus occurs by a new pathway consisting of a patchwork of reactions catalyzed by enzymes from the 3-oxoadipate pathway (catechol 1,2-dioxygenase, muconate cycloisomerase) and the chlorocatechol pathway (maleylacetate reductase) and a trans-DLH.